2001
DOI: 10.1097/00006534-200111000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Variability of the Ilioinguinal and Genitofemoral Nerve: Implications for the Treatment of Groin Pain

Abstract: The differential diagnosis of groin pain must consider problems of the ilioinguinal and/or genitofemoral nerve. These nerves may become injured during hernia surgery or lower quadrant surgical procedures. To treat injury to these nerves, it is critical to understand their anatomic variability. In the present study the pattern of cutaneous nerve branches in the inguinal region was investigated through dissection in 64 halves of 32 human embalmed anatomic specimens. In contrast to usual textual descriptions, fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
132
1
14

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(154 citation statements)
references
References 14 publications
7
132
1
14
Order By: Relevance
“…Looking at the literature, only two anatomical studies have investigated the presence and course of the three inguinal nerves together [55,64], while others have investigated the presence and course of only one or two inguinal nerves [8,9,19,27,39,42,47,50,51,53,62].…”
Section: Is It Possible To See All Three Nerves?mentioning
confidence: 99%
See 1 more Smart Citation
“…Looking at the literature, only two anatomical studies have investigated the presence and course of the three inguinal nerves together [55,64], while others have investigated the presence and course of only one or two inguinal nerves [8,9,19,27,39,42,47,50,51,53,62].…”
Section: Is It Possible To See All Three Nerves?mentioning
confidence: 99%
“…However, this does not imply that they also are identifiable during open hernia repair. For example, in the study by Rab et al [55], the ilioinguinal nerve was incorporated in the genitofemoral nerve, lateral to the deep inguinal ring in 44% of cases. Moosman et al [45] report the same course in 35% of patients.…”
Section: Is It Possible To See All Three Nerves?mentioning
confidence: 99%
“…The classical pattern of distribution and the terminal course of the ilioinguinal and genitofemoral nerve consistent with modern text descriptions were defined in only 20% of cadaveric dissections. 9,10 The dorsal penile nerve (pudendal nerve) is responsible for reflex erections. 11 Damage to the pudendal nerves (that is, Alcock syndrome) leads to erectile dysfunction.…”
Section: Erectionmentioning
confidence: 99%
“…The inguinal nerves are often found to follow variable patterns of distribution [1,5,6]. In a recent study of patients undergoing hernia repair, Al-Dabbagh [1] found that the course of the ilioinguinal and iliohypogastric nerves was only consistent with anatomic texts in 41.8% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Variation in the anatomical course of the inguinal nerves further complicates this already demanding procedure as nerves may be inadvertently compressed or sectioned. Injury to the innervation of this area can lead to postoperative pain [6,7]. For instance, in 49 out of 110 hernia repairs reported by Al-Dabbagh [1], the atypical superficial placement of the ilioinguinal nerve left it particularly vulnerable to transection in the early stages of the operation.…”
Section: Introductionmentioning
confidence: 99%